Application Of Pineapple Extract Addition In Catfish Seed Maintenance At Kampung Perikanan Budidaya Kolam Sumber Rezeki, Tanjung Raja - Yonarta, Danang; Kurniasih, Astri; Mukti, Retno Cahya; Rarassari, Madyasta Anggana (Jurnal Akuakultur Sungai dan Danau, 2025)
Catfish (Clarias sp.) is a species of freshwater fish that is often cultivated. Feed is an important component in the cultivation process to support the growth and survival of fish. The quality of the feed can be improved by adding supplements. One supplement that can be added is the enzyme bromelain which can be obtained from pineapple extract. This research aims to determine the growth and survival of catfish seeds by applying the addition of pineapple extract to the cultivation of catfish seeds in the Sumber Rezeki Pond Cultivation Fishery Village, Tanjung Raja. This research was carried out in the Fisheries Cultivation Village, Sumber Rezeki Pond, Tanjung Raja Selatan Village, Tanjung Raja District, Ogan Ilir Regency, South Sumatra Province in June-July 2024. The results of this research activity with the addition of 6% pineapple extract to catfish feedresulted in absolute length and weight growth of 5.05 cm and 5.47 g, the specific growth rate was 5.4% day-1, the protein efficiency ratio was 4.86, the feed efficiency was 194.2% and the sustainable survival rate by 97%. Air quality during 30 days of maintenance includes temperatures ranging from 26.5-32oC, and pH ranging from 6.4-7.7.